Differences in situational efficiency of goalkeepers depending on match outcome based on Champions League semi finals and finals - Katanic, B.; Nikolic, A.; Ilic, P.; Stankovic, M.; Vitasovic, M. (Sport Science & Practice, 2021)
The aim of this paper is to determine the differences in situational performance of football goalkeepers depending on the outcome of the match, based on the semi-final and final matches of the Champions League, using the method of comparative analysis of the manifestation of goalkeeper`s tactical elements. The analysis was conducted in the semi-final and final matches of the Champions League in the 2016/2017 football season. The paper analyzes the situational elements of the goalkeepers` techniques in the Champions League finals. For the purpose of the research, an observation sheet was formed based on the previous research and personal experience of the author, which was entered into the application "Dartfish EasyTag". Twenty variables were entered into the observation sheet, which are classified into the goalkeeper`s defensive and offensive elements. Video games were downloaded from the Internet, and the analysis was carried out with the help of a portable device, in the "Dartfish EasyTag" application. The results obtained were processed by means of descriptive statistics - total value and difference. After the complete survey, the number of overall situational activities of the goalkeeper is not dependent on the outcome of the match.